2017
DOI: 10.1080/23322039.2017.1293472
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and malaria morbidity in the Jirapa District of Ghana: A count regression approach

Abstract: Malaria potentially affects everyone in the tropics and sub-tropics, however, the poor and vulnerable are worse affected mainly due to the socio-economic constraints that confront them. In Ghana, the Upper West Region, which is the poorest, is one of the worse affected in terms of malaria burden. Given social and economic factors directly relate to malaria morbidity, global malaria control strategy unfortunately has not particularly targeted the effects of socio-economic deprivation on the disease morbidity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…This finding buttresses the point that improving SES of people in endemic areas would enormously help in reducing incidence of malaria [23]. However, the study found no influence of SES on the prevalence of HBV mono-infection, which may be explained by the fact that knowledge and awareness of hepatitis B is generally low in the Ghanaian population, irrespective of social class [38][39][40][41]. Therefore, raising awareness of hepatitis B in all socio-economic facets of the Ghanaian population, could help reduce the burden of the disease and co-infection with malaria.…”
Section: Discussionmentioning
confidence: 86%
“…This finding buttresses the point that improving SES of people in endemic areas would enormously help in reducing incidence of malaria [23]. However, the study found no influence of SES on the prevalence of HBV mono-infection, which may be explained by the fact that knowledge and awareness of hepatitis B is generally low in the Ghanaian population, irrespective of social class [38][39][40][41]. Therefore, raising awareness of hepatitis B in all socio-economic facets of the Ghanaian population, could help reduce the burden of the disease and co-infection with malaria.…”
Section: Discussionmentioning
confidence: 86%
“…Studies at individual or community level often define poverty indicators using a combination of household assets (housing type and ownership, education and sex of the head of household, and crowding in the household) or evidence-based indicators of socioeconomic status (occupation, transportation tools, income, expenditure or asset ownership, and rural location) [ 8 , 11 , 49 ]. For example, a study in Ghana found that social and economic factors are directly related to malaria morbidity, such that income levels for heads of household below the poverty line of USD 1 per day are a significant determinant of malaria morbidity [ 53 ]. A community-based study in Uganda reported that housing improvements and agricultural development to reduce poverty could be effective interventions against malaria [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria remains a hyperendemic disease posing a signi cant public health challenge in Ghana [4], [5]. It is the leading cause of morbidity and mortality despite the scale-up of new malaria preventive and control interventions [6], [7]. Furthermore, malaria ranks rst among outpatient diagnoses, accounting for approximately 40% of all Out-Patient Department diagnoses [8].…”
Section: Introductionmentioning
confidence: 99%